Monetary Aspect of Linkage to Improve Social Life in Javanese Community - Desak Ayu Sriary Bhegawati; Anak Agung Sri Purnami; Made Dian Putri Agustina (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
Monetary issues take an important part in human existence. Financial problems cover many areas in an individual's life, especially the social-social field. The monetary elements in public activities play an important role in determining the degree of social position of a person or group in their current state. In public activities there are several factors that affect a person's level of social position, namely certain financial elements, educational variables, innate elements, and individual work factors. However, in public activities in Indonesia, in general, the monetary element is the most interesting thing that can be used as a benchmark for one's economic welfare. An individual with a high level of abundance will have different ways of life and tendencies compared to an individual who is below the standard level. This social separation certainly has the impact of progress and setbacks in order to support the social life of the community.